Persuasive Communication in Efforts to Preserve the Local Culture of Silat Kuntau in the Era of Millennial - Wanfau, Wanfau; Alfarabi, Alfarabi; G Pramudiasmono, Hajar (UIN Fatmawati Sukarno Bengkulu, 2024)
Pencak silat as one of the local wisdoms of the Indonesian people continues to be introduced to the next generation to help instill a sense of responsibility for preserving local culture. The aim of the research is to try to examine efforts to preserve Kuntau silat culture from a persuasive communication perspective. Descriptive qualitative is a research method with a field research style, namely in-depth research covering everything that happens in the field, with the aim of studying in depth the background of the community situation. The research results show that the communication efforts that take place between trainers and young people use persuasive communication patterns from the bottom up which are caused by two factors, including: 1) Persuasive communication is carried out from parents to the Kuntau silat trainer because the parents want to protect their children. 2) self-awareness regarding how important it is to learn Kuntau silat and the benefits of learning Kuntau silat and how useful it is in life.Keywords: Pencak Silat, Kuntau, Persuasive Communication, Millennial Era Pencak silat as one of the local wisdoms of the Indonesian people continues to be introduced to the next generation to help instill a sense of responsibility for preserving local culture. The aim of the research is to try to examine efforts to preserve Kuntau silat culture from a persuasive communication perspective. Descriptive qualitative is a research method with a field research style, namely in-depth research covering everything that happens in the field, with the aim of studying in depth the background of the community situation. The research results show that the communication efforts that take place between trainers and young people use persuasive communication patterns from the bottom up which are caused by two factors, including: 1) Persuasive communication is carried out from parents to the Kuntau silat trainer because the parents want to protect their children. 2) self-awareness regarding how important it is to learn Kuntau silat and the benefits of learning Kuntau silat and how useful it is in life.